O uso do mobile learning como apoio ao ensino e aprendizagem em Administração - Lima, Thais Vieira de. (2016)
The objective of this study is to present a protocol for the use of mobile technologies available in mobile phones, smartphones and tablets as a complementary modality on the presencial teaching of management. Its about a quali-quantitative research, which used Design Research as methodology. For the elaboration of the protocol it was used a model for rational analysis of mobile education based on experiential learning theory as pedagogical approach. The data collection occured in a private university center in Rio de Janeiro with 62 management students. The results show that the protocol proposed is suitable to the elaboration of strategies and activities of mobile learning because evidences were found which strengthened the adopte theoretical model in this study mainly due the social aspects as interaction; proposal of authentics contexts and formation of learning communities. However, there are barriers to the adoption of mobile learning, as the resistance to change,the low degree of criticality from the students, and the requirement of a solid didactic pedagogical formation from the university professor. Beyond the ferramental nature, the protocol presented in this study intends to contribute with a new perspective about the use of mobile Technologies in the teaching- learning process, through practices able to promote your merger as educational tool.